Effect of TaN intermediate layer on the back contact reaction of sputter-deposited Cu poor Cu2ZnSnS4 and Mo - Zhuk, Siarhei (2020)
Ultrathin tantalum nitride (TaN) intermediate layers (IL) with thickness from 3 nm to 12 nm have been used to limit the undesirable interfacial reaction between molybdenum (Mo) and copper-zinc-tin-sulphide (CZTS). The morphology, chemical and structural properties of the samples were characterized by X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, X-ray diffraction analysis, and scanning transmission electron microscopy (STEM). Time-of-flight secondary ion mass spectrometry (TOFSIMS), energy-dispersive X-ray spectroscopy (EDX), and electron energy loss spectroscopy (EELS) have been used for elemental analysis. Thin TaN IL shows chemical reactivity towards sulphur (S) vapor at 600 °C and the incorporation of S in TaN reduces the S concentration in Mo films at the sub-surface region and thus improves electrical conductivity of sulphurised Mo. The use of a non-stoichiometric quaternary compound CZTS target along with TaN IL enables to minimise thickness of MoS 2 layer and reduce void formation at the Mo/CZTS interface. Furthermore, incorporation of TaN IL improves scratch hardness of CZTS/Mo films to soda-lime glass substrate.